2016
DOI: 10.12669/pjms.325.10655
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of parameters of bone profile and homocysteine in physically active and non-active postmenopausal females

Abstract: Background and objectives:Optimal physical activity is important in attaining a peak bone mass. Physically active women have better bone mineral density and reduce fracture risk as compared to females living a sedentary life. The objective of this study was to compare parameters of bone profile and serum homocysteine levels in physically active and non-active postmenopausal females.Methods:In this cross sectional study postmenopausal females between 50-70 years of age were recruited and divided into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 20 publications
3
6
0
Order By: Relevance
“…20 Our results build on the findings of this preceding study and show that PA is suitable for postpartum women. 20…”
Section: Discussion/conclusionsupporting
confidence: 86%
See 2 more Smart Citations
“…20 Our results build on the findings of this preceding study and show that PA is suitable for postpartum women. 20…”
Section: Discussion/conclusionsupporting
confidence: 86%
“…A previous study has reported on the association between PA and sufficient bone density among postmenopausal women. 20 Our results build on the findings of this preceding study and show that PA is suitable for postpartum women. 20 The risk of a decrease in bone density due to puerperal amenorrhea or lactation in the postpartum period has been reported in a previous study.…”
Section: Discussion/conclusionsupporting
confidence: 86%
See 1 more Smart Citation
“…Body mass index (BMI) and waist to hip ratio (WHR) were calculated by using standard formulas. Bone mineral density (BMD) of postmenopausal females was measured using DBM Sonic Bone profiler manufactured by IGEA, Capri, Italy, Model: BP01 14. Three ml fasting blood was obtained in serum vacutainers.…”
Section: Methodsmentioning
confidence: 99%
“…Another study showed that low mineral density was not associated with participants involved in regular physical activity as compared to those who did not work out daily or have sedentary life styles [11,16] . Similarly,in Nigeria, it has been observed that osteoporosis prevalence was high among younger ages due to non-participation in sports and occupational activities [17] .…”
Section: Discussionmentioning
confidence: 99%